Gambaran Penjualan dan Investası Obat Generık Apotek “X” Kelurahan Kampung Satu Tarakan Menggunakan Analısıs ABC Tahun 2022 - Hendriansyah Hendriansyah; Benazir Evita Rukaya; Syuhada Syuhada (Journal Borneo, 2024)
Pharmacies as health facilities and businesses, require good management to avoid shortages or excess stock of medicines. This research aims to optimize generic drug inventory management at pharmacy "X" using the ABC method. Using a quantitative and retrospective descriptive approach, generic drug sales data for the period January- December 2022 were analyzed. As a result, Group A consisted of 23 drug items with a total sales transaction of 5,877 (69.89%), Group B consisted of 28 drug items with a total sales transaction of 1,654 (19.67%), and Group C consisted of 71 items with the number of sales transactions was 878 (10.44%). In terms of investment value, Group A consists of 31 medicinal items with an investment value of Rp. 39,058,600 (69.63% of the total), Group B consists of 33 medicinal items with an investment value of Rp. 11,290,000 (20.13% of the total), and Group C consists of 58 medicinal items with an investment value of Rp. 5,743,300 (10.24% of the total). The ABC method can optimize generic drug inventory management at pharmacy “X”, enable prioritization based on sales frequency and investment value, and increase efficiency.